Religion of Pandemic: Delegitimization of Authority During the Covid-19 Era - Abdullah, Irwan; Tang, Mulan; Nurhakim, Putri Rahmah; Suprianto, Bibi; Fernando, Henky (Pascasarjana IAIN Pontianak, 2023)
The study delves into the delegitimization of religion during the COVID-19 pandemic, addressing not only the social aspects of religious life but also the social significance of religion itself. It explores how this delegitimization, particularly in Islam, has altered the sacredness of religious life. This qualitative research, utilizing literature review and media analysis, aims to uncover the forms of religious delegitimization that have transformed the face and substance of religion during the pandemic. It investigates 1) how this process has changed the legitimacy of religion, 2) the patterns of belief and worship, and 3) the context and factors underlying this delegitimization. The findings reveal that religious delegitimization during the pandemic is a part of the process of objectifying religion in a health disruption, highlighting changes due to COVID-19 regulations, understanding of religious sacredness, and the authority of religious figures in the context of religion and COVID-19 controversies.